LOW CYCLE FATIGUE LIFE PREDICTIONS OF 15CrMoR PARENT MATERIAL AND WELD METAL - MA Kai; WANG ChuanZhi; DONG JunHua; GAO BingJun (Jixie qiangdu)
Butt-weld specimen has been made for coke drum material 15 Cr MoR. For both parent and weld materials,uniaxial tensile tests and uniaxial ratcheting tests have been conducted under different temperatures. The OW-II kinematic hardening constitutive model has been used to predict the material ratcheting effect using the experimental data obtained. Test results show that the OW-II model can well predict ratcheting strain rates for the stable period. Based on the obtained uniaxial tensile test data,basic parameters for predicting low cycle fatigue life have been obtained. The MSRS model has been used to predict the fatigue lives of the parent material and weld metal. The predicted results are within the 2 times error band and are uniformly distributed on both sides of 45 ° line accurately. Furthermore,the ratcheting strain rate and the strain amplitude for the stable period are obtained for the parent metal and the weld metal respectively by the OW-II kinematic hardening constitutive model under the same conditions. The MSRS model predicts that the fatigue life of the parent material is significantly lower than that of the weld metal and during the stable period the ratcheting strain rate of parent material is significantly higher than that of the weld metal.